Literarni turizem in priložnosti za njegov razvoj v Sloveniji: Louis Adamič – pisatelj z zgodbo, ki povezuje Slovenijo, Balkan in Združene države Amerike - Potočnik Topler, Jasna (University of Maribor Press, 2020)
Literary Tourism and Opportunities for its Development in Slovenia: Louis Adamič – A Writer with a Story that Connects Slovenia, the Balkans and the United States of America. Scientific monograph Literary Tourism and Opportunities for Its Development in Slovenia: Louis Adamič – A Writer with a Story that Connects Slovenia, the Balkans and the United States of America presents literary tourism from the analytical perspective and evaluation of literary heritage and its inclusion into the tourism offer. The monograph brings a literature review of the area of literary tourism and explains literature in the context of tourism, literary tourism and cultural experiences. The monograph is focused on the works by Louis Adamič (1898–1951), especially on the novels The Native’s Return and My Native Land, and in which the areas of tourism, literary theory and literature are intertwined. The monograph brings an analysis and evaluation of literary heritage by Louis Adamič as the resource of future literary tourism development in Slovenia, and by presenting literary tourism concepts along with the methodology of the area the book also offers some recommendations on the possible inclusion of Adamič’s heritage into the tourism offer. Thus, to tourism destination managers and other tourism stakeholders the monograph may serve as a handbook in creating new tourism products and in improving the existing tourism offer.